Bulk Fill flow resin contraction using 3D finite element model and calibration by Fiber Bragg Grating measurement. Issue 14 (11th July 2020) - Antunes Junior, Claudio; Mercuri, Emílio Graciliano Ferreira; Franco, Ana Paula Gebert de Oliveira; Costa, Manoella; Karam, Leandro Zen; Kalinowski, Hypolito José; Gomes, Osnara Maria Mongruel
Abstract: Contraction due to polymerization of dental resin can cause failure on the adhesive interfaces, can lead to problems such as the appearance of gaps in the interfaces, postoperative sensitivity, pulp damage and the return of the caries. The objective of this work is the study of stresses on the dental adhesive that are generated by the process shrinkage of resin associated with biting forces. A laboratory experiment measured the strains and temperature inside the Filtek TM Bulk Fill Flow resin during the process of polymerization using Fiber Bragg Grating sensors in an ex vivo tooth. From tomographic images a three-dimensional geometric model of the tooth was reconstructed. A pre-tension was calibrated to simulate the residual contraction on the resin 3 D model. Finally, an Finite Element Method analysis was performed to access the adhesive stresses at the interface enamel/dentin with the adhesive, considering as loading the residual polymerization contraction of the dental resin and also biting loads. The model was able to represented the strain obtained in the laboratory experiment. The results of the stress analysis shows that the outer regions of adhesive are more prone to failure, as veried by dental surgeons in clinical practice.